Abordări STEAM ale dronelor în predarea disciplinelor exacte [Articol] - Afanas, Dorin; Brigalda, Arina (Editura USM, 2024)
In order to meet the requirements of the modern educational process, the teaching staff is always looking for another way of teaching-learning-evaluating the curricular subjects, relevant to the students' interests. Such a way can be given to us by drones, because with their help we can visualize the world with new eyes. Educational drones, in specialized literature, are also called aerial vehicles without a human pilot on board. This article presents examples of STEAM approaches to the application of drones in mathematics, physics and technology education. Thus, the following themes are researched: linear dependence, proportionality, quadratic function and quadratic relationship, area calculation, gravitational acceleration. The application of drones in other fields is also discussed.
STEAM approaches to drones in the teaching of exact disciplines
Keywords: drone; addiction; STEAM; proportionality; acceleration